Concentrador solar para dessalinização de água: projeto e construção - Prado, Gustavo Otero (2011)
Energy is the driving force of the transformations of nature. The human instinct is scheduled to search for energy sources in order to their survival and comfort but the indiscriminate and ambitious use disrupts the natural balance resulting in an environment increasingly inhospitable and a saturation of natural resources compromising even the availability of drinking water on the planet. Energy sources like oil, coal and nuclear ssion are not renewable and constantly produce polluting residues. Alternatively to have renewable energy sources such as wave and tidal, geothermal and wind power. None, however, is so abundant and available as solar energy. Regarding the shortage of water today, according to Wambeke (2007), more than 1.1 billion people do not have the minimum amount of water to survive. This work was inspired by the use of solar energy for turn salt water into potable water. To this was planned and built a parabolic trough solar concentrator and an evaporation plant to be connected to the solar concentrator. The values used to build the project were based on local weather conditions and with the goal of reaching temperatures higher than 100 C in the uid inside the pipe. For the denition of dimensional trough was seen that a parabolic curve succeeded in shifting the focus without scattering, that would take a trough area with 20 m2 and a pipe with 43 m to reach the design temperature. It was noticed that the wind is largely responsible for the loss of heat by convection and that for smaller ow reaches the temperature equilibrium of the system with a smaller length of pipe. There was also a preliminary characterization of the heating system in order to observe the maximum temperatures reached. It might be noted that the maximum temperature was 105 C by using the ow through the thermosyphon.